Training the Next Generation - Kopp, Susan (The Hastings Center report, 2012)
As an educator in an urban veterinary technology program, I often encounter students beginning their professional studies who are passionate about their commitment to a career working with animals. Typically, they have also firmly decided that they will never accept a job in the animal research field. They object to animal research in general because of what they assume is the abject mistreatment of animals housed in laboratories. Chatting again with these students two years later as they prepare for graduation, however, I am increasingly finding that many reconsider those firm convictions. In fact, even in a strong job market for veterinary technicians, some of these graduates are actually choosing to enter the laboratory animal care field. What is causing such an about-face?